2015
DOI: 10.1159/000433552
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Discomfort Caused by a Unilateral Hearing Loss in People Suffering from a Total Bilateral Vestibular Loss

Abstract: The quality of life of patients suffering from a bilateral vestibular loss is severely altered. Patients mainly complain of oscillopsia, imbalance, and spatial disorientation. Up to now, there is no efficient treatment. Some teams around the world are working on the development of a vestibular implant for the restoration of the vestibular function based on the concept similar to that of a cochlear implant, stimulating the neural vestibular pathways through electrical pulses. There are different potential stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, only some patients explicitly indicated single-sided deafness as an unacceptable risk factor, whereas other patients explicitly indicated single-sided deafness as an acceptable risk factor. Previous research has shown that patients with BV have more pronounced negative expectations about possibly having unilateral hearing loss than healthy people and people who are actually suffering from unilateral hearing loss [ 34 ]. These latter do not perceive their unilateral hearing loss as a major handicap at all [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only some patients explicitly indicated single-sided deafness as an unacceptable risk factor, whereas other patients explicitly indicated single-sided deafness as an acceptable risk factor. Previous research has shown that patients with BV have more pronounced negative expectations about possibly having unilateral hearing loss than healthy people and people who are actually suffering from unilateral hearing loss [ 34 ]. These latter do not perceive their unilateral hearing loss as a major handicap at all [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that patients with BV have more pronounced negative expectations about possibly having unilateral hearing loss than healthy people and people who are actually suffering from unilateral hearing loss [ 34 ]. These latter do not perceive their unilateral hearing loss as a major handicap at all [ 34 , 35 ]. It is important to acknowledge that the trade-off between improved function and potentials risks related to the surgical procedure (e.g., hearing loss) is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Adults' responses, direct or proxy, can differ from those of children. Additionally, while Priwin and colleagues found that their participants complained relatively often about the negative impact of UHI in everyday communication situations, Gay and colleagues (2015) [80] had just the opposite result. Adults (N = 20) of their study did not perceive their UHI as a major handicap.…”
Section: Accepted Manuscriptmentioning
confidence: 97%